Plasma levels of neurology-related proteins are associated with cognitive performance in an older population with overweight/obesity and metabolic syndrome - Martí Llaurador-Coll; Santiago Rios; Jesus F. García-Gavilán; Nancy Babio; Elisabet Vilella; Jordi Salas-Salvadó (GeroScience, 2023)
Cognitive impairment is present in a broad spectrum of medical conditions and in aging. Here, we aimed to identify plasma proteins related to cognitive function in a sample of older adults with overweight/obesity and metabolic syndrome. A total of 129 subjects (mean age 64.7 years; 36% females) were grouped according to low (l-GCF, N =65) or high (h-GCF, N =64) global cognitive function and matched according to education, sex, age, and body mass index. Cognitive performance was assessed using neuropsychological tests. Plasma levels of 92 neurology-related proteins were assessed using a proximity extension assay. An elastic net regression analysis was used to identify proteins more associated with cognitive performance. Additionally, the protein expression levels were compared between the two groups by means of a t -test with false discovery rate correction. Pearson correlations were used to assess associations between the protein levels and scores from the neurocognitive tests. Six proteins (alpha-2-MRAP, HAGH, Siglec-9, MDGA1, IL12, and EDA2R) were identified as potential contributors to cognitive performance, remaining significantly increased in l-GCF compared to h-GCF participants after correction for multiple testing. Negative correlations ( r = −0.23 to −0.18, i.e., lower protein levels, higher cognitive function) were found between global cognitive function and Siglec-9, NMNAT1, HAGH, LXN, gal-8, alpha-2-MRAP, IL12, PDGF-R-alpha, NAAA, EDA2R, CLEC1B, and LAT. Mini-mental state examination z scores showed the strongest correlations with protein levels, specifically negative correlations with CLEC1b, LXN, LAT, PLXNB3, NMNAT1, gal-8, HAGH, NAAA, CTSS, EZR, KYNU, MANF ( r =−0.38 to −0.26) and a positive correlation with ADAM23 ( r = 0.26). In summary, we identified several plasma proteins that were significantly associated with cognitive performance in older adults with obesity and metabolic syndrome, although further research is needed to replicate the results in larger samples and to include a predictive perspective.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Lynx eats cat: disease risk assessment during an Iberian lynx intraguild predation - F. Nájera; S. Sánchez-Cuerda; G. López; T. Del Rey-Wamba; C. Rueda; N. Vallverdú-Coll; J. Panadero; M. J. Palacios; J. V. López-Bao; J. Jiménez (European Journal of Wildlife Research, 2019)

Ecological role and historical trends of large pelagic predators in a subtropical marine ecosystem of the South Atlantic - Hugo Bornatowski; Ronaldo Angelini; Marta Coll; Rodrigo R. P. Barreto; Alberto F. Amorim (Reviews in Fish Biology and Fisheries, 2018)

Human diet and the chronology of neolithic societies in the north-east of the Iberian Peninsula: the necropolises of Puig d’en Roca and Can Gelats (Girona, Spain) - Juan F. Gibaja; Maria Fontanals-Coll; Stephanie Dubosq; F. Xavier Oms; Anna Augé; Francisco Javier Santos; Berta Morell; M. Eulàlia Subirà (Archaeological and Anthropological Sciences, 2017)

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Growth and yield of mixed versus pure stands of Scots pine (Pinus sylvestris L.) and European beech (Fagus sylvatica L.) analysed along a productivity gradient through Europe - H. Pretzsch; M. del Río; Ch. Ammer; A. Avdagic; I. Barbeito; K. Bielak; G. Brazaitis; L. Coll; G. Dirnberger; L. Drössler; M. Fabrika; D. I. Forrester; et al. (European Journal of Forest Research, 2015)

Modelling dynamic ecosystems: venturing beyond boundaries with the Ecopath approach - M. Coll; E. Akoglu; F. Arreguín-Sánchez; E. A. Fulton; D. Gascuel; J. J. Heymans; S. Libralato; S. Mackinson; I. Palomera; C. Piroddi; L. J. Shannon; J. Steenbeek; et al. (Reviews in Fish Biology and Fisheries, 2015)

Risk of intrauterine growth restriction among HIV-infected pregnant women: a cohort study - M. López; M. Palacio; A. Goncé; S. Hernàndez; F. J. Barranco; L. García; M. Loncà; J. O. Coll; E. Gratacós; F. Figueras (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Exploring Patterns of Seafood Provision Revealed in the Global Ocean Health Index - Kristin M. Kleisner; Catherine Longo; Marta Coll; Ben S. Halpern; Darren Hardy; Steven K. Katona; Frédéric Le Manach; Daniel Pauly; Andrew A. Rosenberg; Jameal F. Samhouri; Courtney Scarborough; U. Rashid Sumaila; et al. (Ambio, 2013)

Serotype 3 is a common serotype causing invasive pneumococcal disease in children less than 5 years old, as identified by real-time PCR - L. Selva; P. Ciruela; C. Esteva; M. F. Sevilla; G. Codina; S. Hernandez; F. Moraga; J. J. García-García; A. Planes; F. Coll; I. Jordan; N. Cardeñosa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Aspirin induces apoptosis in human leukemia cells independently of NF-κB and MAPKs through alteration of the Mcl-1/Noxa balance - Daniel Iglesias-Serret; Maria Piqué; Montserrat Barragán; Ana M. Cosialls; Antonio F. Santidrián; Diana M. González-Gironès; Llorenç Coll-Mulet; Mercè de Frias; Gabriel Pons; Joan Gil (Apoptosis, 2010)

Biological patterns and ecological indicators for Mediterranean fish and crustaceans below 1,000 m: a review - F. Sardà; J. B. Company; G. Rotllant; M. Coll (Reviews in Fish Biology and Fisheries, 2009)

Hyperspectral indices for detecting changes in canopy reflectance as a result of underground natural gas leakage - M. F. Noomen; K. L. Smith; J. J. Colls; M. D. Steven; A. K. Skidmore; F. D. Van Der Meer (International Journal of Remote Sensing, 2008)

Effect of Spirostane Analogues of Brassinosteroids on Callus Formation and Plant Regeneration in Lettuce (Lactuca sativa) - M. Núñez; W.J. Siqueira; M. Hernández; M.A.T. Zullo; C. Robaina; F. Coll (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Abstracts - Danuta Babula; Malgorzata Ruminska; Jan Sadowski; Josep M. Folch; Ramona Natacha Pena; Agustina Coll; Armand Sánchez; James M. H. Kijas; Leif Andersson; Dušan Kordiš; Franc Gubenšek; Gregor Majdič; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

In situ measurements of skeletal muscle power output using new capacitive strain gauge - P. G. Cooper; G. J. Wilson; D. T. A. Hardman; O. Kawaguchi; Y. -F. Huang; A. Martinez-Coll; R. Carrington; E. Puchert; R. Crameri; C. Horam; S. N. Hunyor (Medical & Biological Engineering & Computing, 1999)

A model to study fish DNA immersion vaccination by using the green fluorescent protein - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; R. Blasco; J. M. Coll (Journal of Fish Diseases, 1999)

G disulphide bond native conformation is required to elicit trout neutralizing antibodies against VHSV - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; J. M. Coll (Journal of Fish Diseases, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Sequential G-banding FISH on human sperm chromosomes - P. Colls; C. Templado; O. Martinez-Pasarell; F. Darroudi; A. T. Natarajan (Chromosome Research, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Chromosome segregation in a man heterozygous for a pericentric inversion, inv(9)(p11q13), analyzed by using sperm karyotyping and two-color fluorescence in situ hybridization on sperm nuclei - P. Colls; J. Blanco; O. Martínez-Pasarell; F. Vidal; J. Egozcue; C. Márquez; M. Guitart; C. Templado (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Neutralizing-enhancing monoclonal antibody recognizes the denatured glycoprotein of viral haemorrhagic septicaemia virus - F. Sanz; J. M. Coll (Archives of Virology, 1992)

The free nucleocapsids of the viral haemorrhagic septicaemia virus contain two antigenically related nucleoproteins - B. Basurco; F. Sanz; M. A. Marcotegui; J. M. Coll (Archives of Virology, 1991)